The analysis of occupational safety and health practices that affect the labor risk in Pembangunan Pertanian Melaka Sdn Bhd Oil Palm Estate / Mohd Khairul Azam Azali - Azali, Mohd Khairul Azam (Faculty of Plantation and Agrotechnology, 2017)
Occupational health and safety is a process of ensuring that people stay safe and healthy in the workplace to increase workers capacity to perform. The purpose of this study was to evaluate the OSH implementation, knowledge, and participation of plantation workers as well as to identify the existence of a relationship of OSH practices with accident’s rate. A simple random sampling techniques was conducted to select 40 workers out of the 45 population who worked with Pembangunan Pertanian Melaka Sdn Bhd (PPMSB), Merlimau, Melaka. The data were collected using structured questionnaire and analyzed by using Statistical Package for Social Sciences (SPSS) version 20. The data obtained were then analyzed by using the descriptive statistic, anova, correlation and multiple regression. The result indicated that there are significant difference between all practices since the p-value is 0.001 less than 0.05. The result of the study also revealed that each of the practices which is implementation, knowledge and participation had a significant effect on accident’s rate when r² value obtained was 0.383 explains that 38.3% of the variance associated with the rate of accidents. The result also showed that the most dominant variable towards accident’s rate is implementation with the β value is 0.676, followed by a factor of participation with the β value is 0.018 and knowledge with the β value is -0.360. The result also found that there was a medium positive relationship between implementation towards rate of accidents. Since the significant value is 0.000 less than the significant level of 0.05 (2-tailed) and there was no relationship between knowledge and participation towards rate of accidents.